Nocturnal animals [videorecording (DVD)] - Ford, Tom, 1961-; Adams, Amy; Gyllenhaal, Jake, 1980-; Shannon, Michael, 1974-; Fisher, Isla, 1976-; Hammer, Armie, 1986-; Linney, Laura; Wright, Austin McGiffert, 1922-2003 (Universal Pictures Home Entertainment, 2017)
Susan is living through an unfulfilling marriage when she receives a package containing a novel manuscript from her ex-husband, Edward. The novel is dedicated to her but its content is violent and devastating. Susan cannot help but reminisce over her past love story with the author. Increasingly she interprets the book as a tale of revenge, a tale that forces her to re-evaluate the choices that she has made, and reawakens a love that she feared was lost.